Organizational change, innovation and business development : the impact of non-technological innovations - Popowska, Magdalena; Wasilczuk, Julita (New York, NY : Routledge, 2023)
"This volume presents a collection of different views and perspectives, featuring both theoretical and empirical contributions, to provide deep insight into the role of innovation and of non-technological innovations (NTIs) in contemporary business. It illustrates how NTIs encourage organizational development as well as competitive advantage. Chapters display a variety of research methods, both qualitative and quantitative, including case studies, best practices, surveys, novel approaches to interpretations, concepts and theories. Together they contribute to a significant extension of the existing knowledge on non-technological innovations and their role in organizations. This volume highlights the effects of marketing and organizational innovation strategies on companies' innovation and overall performance, while demonstrating that the effects of NTI may vary depending on the phase of the innovation process, and how it differs within small, medium and large enterprises from manufacturing and service industries. It explores the bidirectional relationship between technological innovation (TI) and NTI, and considers the competences needed to implement NTI. The book is written for scholars and academic professionals from a wide variety of disciplines addressing issues of organizational change and innovation, new management techniques and strategies, and the sustainable growth of organizations. It may also be an interesting source of knowledge for graduate and postgraduate students in management"--
OCLC-licensed vendor bibliographic record.
Keywords: Organizational change; Industrial management; Leadership; Communication in organizations; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Development / Sustainable Development